Effect of raised level α-linolenic fatty acid diet on broiler meat quality - Pálfy, Tamás; Hermán, Istvánné; Lugasi, Andrea; Vadáné Kovács, Mária; Erdélyi, István; Gundel, János (Acta Agraria Debreceniensis, 2007)
The aim of our investigation was to determine the effects of increased α-linolenic content in food on the colour, total pigment content, organoleptic characteristics and oxidative stability of poultry meat. The experiment was carried out with 1200 Ross-308 cock chicklings. Birds were fed three-phase diets, contained four different fat sources: lard, sunflower oil, flaxseed oil and soybean oil. According to the experiment, the different oil sources had no effect on growth performance, but the fatty acid composition of diets was reflected in the meat fatty acid profile. We could detect just slight change in colour in the treated meat, which was not caused by the decreased pigment content. The detected change in colour during the storage was not in relation to initial PUFA content. TBA level did not prove the accelerated lipid peroxidation which was expected in case of higher α-linolenic containing the meat. The data obtained in meat storage trial, could not prove clearly the negative effect of the higher α-linolenic content of the meat.